In the circle of loneliness and addiction - basedon an example of alcoholism - Borczykowska-Rzepka, Maria; Skwarek, Beata (W kręgu samotności i uzależnienia na przykładzie choroby alkoholowej, 2023)
Alcoholism is a chronic, incurable disease. Its essence is the psychophysical dependence on the psychoactive substance constituted by alcohol. This article discusses the problem of loneliness experienced by young adults diagnosed with alcoholism. The aim of the study was to estimate the levels of global loneliness as well as emotional, psychological and existential loneliness in a group of young adults struggling with alcohol dependence, and the subject of the study was to carry out an analysis of the phenomenon of loneliness in a group of young adults (men and women) who are addicted to alcohol.
Zeszyty Naukowe Collegium Witelona, nr 47(2)/2023, s. 51-64
Keywords: alcoholism; addiction; loneliness; young adults